2009
DOI: 10.1176/appi.ps.60.7.943
|View full text |Cite
|
Sign up to set email alerts
|

Help Seeking and Perceived Need for Mental Health Care Among Individuals in Canada With Suicidal Behaviors

Abstract: Although suicidal ideation and suicide attempts represent a significant source of evaluated need associated with help seeking and perceived need over and above the presence and severity of mental disorders, a significant proportion of individuals with suicidal behaviors did not receive care and did not perceive a need for care. Future research should be directed toward finding better ways to identify these individuals and address barriers to their care and other factors that may interfere with their receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 0 publications
0
40
2
Order By: Relevance
“…In our study, in contrast to Pagura et al (2009), almost all associations found were explained by severity of the axis-I symptomatology. Pagura et al included respondents with or without a mental disorder and adjusted for the amount of disorders, including alcohol and drug dependence.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…In our study, in contrast to Pagura et al (2009), almost all associations found were explained by severity of the axis-I symptomatology. Pagura et al included respondents with or without a mental disorder and adjusted for the amount of disorders, including alcohol and drug dependence.…”
Section: Discussioncontrasting
confidence: 93%
“…Brook et al (2006), Pirkis et al (2001b) and Pagura et al (2009) found higher percentages. Although this might be caused by the use of a broader definition of service use, it could also be explained by the low financial barriers and easy access to specialized mental-health care in the Netherlands.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Difficulty in admitting the problem and seeking help are common characteristics among the Chinese, which affects their propensity for help-seeking behaviour and in turn increase their susceptibility to mental health issues (Pagura, Fotti, Katz, & Sareen, 2009). Such behaviours are seen as a sign of weakness and vulnerability, which produces the feared reality of losing respect in the community (Basu, 1991;GAMECS Project, 1999).…”
Section: Help-seeking Attitudesmentioning
confidence: 99%
“…In this sense, Pagura refers to the existence of a large number of people who, in spite of finding themselves in a high risk suicide situation, do not realize the magnitude of this problem. Thus, they never get to ask for any kind of help, neither from relatives nor from health professionals, what limits considerably the intervention of health professionals (27) . In this same concept, there are many people who, after having had a suicide attempt, do not maintain a correct continuation of the psychiatric treatment or they stop with the medical supervision (28) .…”
mentioning
confidence: 99%